2000
DOI: 10.3122/15572625-13-4-233
|View full text |Cite
|
Sign up to set email alerts
|

Routine Vaginal Cuff Smear Testing in Post-Hysterectomy Patients With Benign Uterine Conditions: When Is It Indicated?

Abstract: Background: By the age of 60 years, an estimated 33% of women will have undergone a hysterectomy. Approximately 85% of these hysterectomies are performed for benign disease. The object of this study was to evaluate cytologic findings from vaginal cuff smears in patients who have undergone hysterectomy for benign uterine conditions. ' Methods: We conducted a community-based retrospective study and foilow-up of women with vaginal cuff cytologic smears who had had a hysterectomy for benign uterine conditions. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In conclusion, given the results of the current study and those of several others, [5][6][7][8][9][10]15 we agree with the current USPTF recommendation that continued V-Pap testing is not useful in women S/P T-hyst for benign disease, especially in women 65 yr. The cost-savings may be used to screen women at high risk for developing this preventable cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, given the results of the current study and those of several others, [5][6][7][8][9][10]15 we agree with the current USPTF recommendation that continued V-Pap testing is not useful in women S/P T-hyst for benign disease, especially in women 65 yr. The cost-savings may be used to screen women at high risk for developing this preventable cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have shown similar lack of screening necessity. [5][6][7][8][9][10] On the other hand, several other studies have reported vaginal neoplasia or carcinoma in women S/P T-Hyst for benign disease. [11][12][13] VAIN occurs most often among women with cervical intraepithelial neoplasia (CIN) or vulvar intraepithelial neoplasia (VIN).…”
Section: Introductionmentioning
confidence: 99%
“…No benefit in patient outcomes was observed. 123 A cross-sectional study of 5,330 screening cytology tests in women after a hysterectomy found 1 case of dysplasia and no cancers. 124 In a study of 193 women with CIN at hysterectomy, the incidence of abnormal vaginal cuff cytology at least 2 years after hysterectomy was 0.7 per 1,000; at 20 years, 96.5% of the women continued to have normal cytology.…”
Section: Evidencementioning
confidence: 99%
“…A retrospective study of 220 women selected at random from 2066 women with a previous hysterectomy for benign conditions and followed for an average of 89 months identified 7 patients (3%) with intraepithelial cytologic abnormalities, but no vaginal cancers. No benefit in patient outcomes was observed 123. A cross‐sectional study of 5330 screening cytology tests in women after a hysterectomy found one case of dysplasia and no cancers 124…”
Section: Recommendations Rationale and Evidencementioning
confidence: 99%